STUDY THE EFFECT OF COCONUT WATER AND SOME GROWTH REGULATORS ON ORCHID PROPAGATION IN VITRO - Dima. G. A. Alghanimy; Lamiaa. K. J. Alamery (The Iraqi Journal of Agricultural science)
The study was conducted in the Central Laboratory of Plant Tissue Culture - College of Agricultural Engineering Sciences - University of Baghdad for the period from October 2021 to August 2022 with the aim of tissue propagation of the Phalaenopsis amabilis L. orchid plant. The study consisted of five sequential experiments (sterilization, initiation, multiplication, rooting, and acclimatization) in order to obtain the best treatment for the next experiment. The results showed that the best treatment for sterilizing the nodules was 15 ml of commercial bleach for 15 minutes. As for the Initiation stage, the nodules were stimulated on MS medium containing 60 ml L-1 coconut water, which amounted to 100%. As for the multiplication stage, the interaction between BA and NAA showed a significant effect on the average number of shoots, their length, and the number of leaves, where the concentration of 2.5 mg L-1 BA in interaction with 1 mg L-1 of NAA produced the highest rate of shoots number (4 shoots. explants-1), leaves number.shoot-1 (4 shoot-1). The best medium for rooting the shoots was using MS medium half the strength of salts prepared with IBA at a concentration of 1 mg L-1 Where it produced the highest rate of rooting (100%), number of roots (9 root shoot -1) and root length (6 cm.). As for acclimatization, the highest surviving rate (90%) was obtained in the mediums: river soil, peat moss, Perlite and tree bark, peat moss, perlite at a ratio of 1:1:1 for each.